RELATIONSHIP CORAL REEF COVER WITH REEF FISH ABUNDANCE IN THE WATERS OF MIANG ISLAND, SANGKULIRANG, KUTAI EAST, EAST KALIMANTAN - Luthfi, Oktiyas Muzaky (Journal of Environmental Engineering and Sustainable Technology, 2021)
Miang Island is located at coordinates 118° 0' 20" E - 0° 44' 0" N which is administratively in Sangkulirang District, East Kutai Regency, East Kalimantan. Coral reefs on Miang Besar Island have an area of ± 218.8 ha, with the best coral cover in the waters of Sangkulirang District and one of the best in East Kutai Regency. Reef fish have an active role in coral reef ecosystems because they can be indicators of the health of coral reef ecosystems and can be used to measure the level of suitability of their habitats. If the condition of the coral is damaged, the number of reef fish that inhabit it will decrease because the habitat does not meet the availability of food ingredients and the loss of breeding grounds. Coral reef data retrieval using the UPT method and reef fish using the UVC method. The percentage of coral cover on Miang Island is in the moderate to bad category where the average percentage of cover is 21% which is in poor condition (<25%). The total abundance of fish at station 1 was 0.45 ind./m3, station 2 was 0.10 ind./m3, station 3 was 0.06 ind./m3, and station 4 was 0.09 ind./m3. The genus Acropora is the dominant coral genus at all stations and the Pomacentridae family is the dominant family of reef fish at all stations. The relationship between the percentage of coral cover and the abundance of reef fish is very strong with an R2 value of 72.13%.